Internet Gaming Disorder Among Junior High School Adolescents in Jakarta: A Comparative Analysis Between Public and Private Schools - Eva Suryani; Tjhin Wiguna; Listya Tresnanti Mirtha; Kristiana Siste; Rini Sekartini; Sabarinah Sabarinah; Alida R. Harahap; Luh Nyoman Alit Aryani (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: The increasing availability of mobile games and expandinng access to devices have contributed to the growing prevalence of Internet Gaming Disorder (IGD), particularly among adolescents. The IGD is associated with impaired well-being and functioning, including sleep, psychological, academic, and social problems. However, evidence regarding effective school-based interventions remains limited. This study aimed to explore the prevalence of IGD among junior high school students in public and private schools in Jakarta, Indonesia. Methods: An analytic observational study with a cross-sectional design was conducted among 2,320 junior high school students from January to August 2025. Demographic data were collected using a basic questionnaire, and IGD was assessed using the Internet Gaming Disorder Test-10 (IGDT-10). Data were analyzed using the Chi-square test and Mann–Whitney test with SPSS version 23.0Results: The prevalence of Internet Gaming Disorder (IGD) among junior high school adolescents in Jakarta was 2.2%. In private school, IGD was significantly associated with duration of gaming ≥4 hours/day and male gender, whereas in public school, IGD was significantly associated with the use of multiple gaming devices.Conclusions: The prevalence of IGD among junior high school students in Jakarta was 2.2%. Factors associated with IGD varied between public and private schools, suggesting that prevention strategies should be tailored to the school context. Early identification of excessive gaming behaviors may support adolescent well-being and healthy development.